2011
DOI: 10.1186/1476-4598-10-46
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility of metastatic cells derived from human prostate and colon cancer cells to TRAIL and sensitization of TRAIL-insensitive primary cells to TRAIL by 4,5-dimethoxy-2-nitrobenzaldehyde

Abstract: BackgroundTumor recurrence and metastasis develop as a result of tumors' acquisition of anti-apoptotic mechanisms and therefore, it is necessary to develop novel effective therapeutics against metastatic cancers. In this study, we showed the differential TRAIL responsiveness of human prostate adenocarcinoma PC3 and human colon carcinoma KM12 cells and their respective highly metastatic PC3-MM2 and KM12L4A sublines and investigated the mechanism underlying high susceptibility of human metastatic cancer cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…Abrogation of DNA-PKcs in the cells induced the upregulation of DR5 and active caspase-8, -9, and -3. In accordance with the same approach, 4, 5-dimethoxy-2-nitrobenzaldehyde (DMNB), a specific inhibitor of DNA-PK, potentiated TRAIL-induced cytotoxicity and apoptosis in relatively TRAIL-insensitive KM12 and PC3 cells Kim et al (2011). Consistent with the same concept, K562/R3 cells, a stable TRAIL-sensitive variant isolated from human K562 leukemic cells, displayed down regulation of DNA-PK/Akt pathway and a high responsiveness to TRAILmediated growth inhibition and apoptosis.…”
Section: Dna-pk: Major Stumbling Block In Trail Toward Therapysupporting
confidence: 55%
“…Abrogation of DNA-PKcs in the cells induced the upregulation of DR5 and active caspase-8, -9, and -3. In accordance with the same approach, 4, 5-dimethoxy-2-nitrobenzaldehyde (DMNB), a specific inhibitor of DNA-PK, potentiated TRAIL-induced cytotoxicity and apoptosis in relatively TRAIL-insensitive KM12 and PC3 cells Kim et al (2011). Consistent with the same concept, K562/R3 cells, a stable TRAIL-sensitive variant isolated from human K562 leukemic cells, displayed down regulation of DNA-PK/Akt pathway and a high responsiveness to TRAILmediated growth inhibition and apoptosis.…”
Section: Dna-pk: Major Stumbling Block In Trail Toward Therapysupporting
confidence: 55%
“…Colonospheres show increased levels of total β‐catenin, cyclin‐D1, and c‐Myc, and upregulation of c‐Myc greatly enhances the formation of colonospheres . c‐Myc can upregulate and downregulate the expression of DR5 and c‐FLIP, respectively, and knockdown of the c‐Myc gene reduces the responsiveness to TRAIL and the expression of DR5 in PC3‐MM2 cells . Therefore, c‐Myc, which is required for properties of CSCs, may be responsible for hypersensitivity of HCT‐15 colony and CD44 + cells to TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…(35) c-Myc can upregulate and downregulate the expression of DR5 and c-FLIP, respectively, (25,26) and knockdown of the c-Myc gene reduces the responsiveness to TRAIL and the expression of DR5 in PC3-MM2 cells. (44) Therefore, c-Myc, which is required for properties of CSCs, may be responsible for hypersensitivity of HCT-15 colony and CD44 + cells to TRAIL. This hypothesis was supported by a previous report indicating that SP-cells with higher levels of c-Myc, which activates DR4 transcription, have a higher sensitivity to TRAIL than non-SP cells.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of PC-3 cells can be in part explained by aneuploidy (more than 60 chromosomes), their complex form and great stability of their genome, and the huge variety in DNA repair machinery [48][49][50]. These elements could be blocked or inhibited by RG003 as it has been shown that the inhibition of the DNA repair machinery sensitizes cancer cells to apoptotic agents such as TRAIL [51,52].…”
Section: Discussionmentioning
confidence: 97%